Fe3O4@mSiO2 core–shell nanocomposite capped with disulfide gatekeepers for enzyme-sensitive controlled release of anti-cancer drugs. Issue 6 (8th December 2014) - Yang, Chunyu; Guo, Wei; Cui, Liru; An, Na; Zhang, Ting; Guo, Gang; Lin, Huiming; Qu, Fengyu
Abstract : Multifunctional nanocarriers based on the magnetic Fe3 O4 nanoparticle core and bis-(3-carboxy-4-hydroxy phenyl) disulfide modified mesoporous silica shell were synthesized for cancer treatment through passive targeting and enzyme-sensitive drug release. Abstract : Multifunctional nanocarriers based on the magnetic Fe3 O4 nanoparticle core and bis-(3-carboxy-4-hydroxy phenyl) disulfide (R–S–S–R1 ) modified mesoporous silica shell (Fe3 O4 @mSiO2 @R–S–S–R1 ) were synthesized for cancer treatment through passive targeting and enzyme-sensitive drug release. Anti-cancer drug doxorubicin (DOX) was used as the model cargo to reveal the release behavior of the system. The drug loading system (DOX–Fe3 O4 @mSiO2 @R–S–S–R1 ) retains the drug until it reaches the tumor tissue where glutathione reductase (GSH) can degrade the disulfide bonds and release the drug. Furthermore, the grafting amount of R–S–S–R1 can be used to adjust the release performance. All the release behaviors fit the Higuchi model very well and the release kinetics are predominated by disulfide bond degradation and mesoporous structure. With good bioactivity and targeted release performance, the system could play an important role in the development of intracellular delivery nanodevices for cancer therapy.